2018
DOI: 10.3389/fphar.2018.00927
|View full text |Cite
|
Sign up to set email alerts
|

Sp1, Instead of AhR, Regulates the Basal Transcription of Porcine CYP1A1 at the Proximal Promoter

Abstract: Pigs are commonly used as an animal model to evaluate the toxic effects of exogenous compounds. Cytochrome P450 1A1 (CYP1A1) metabolizes numerous exogenous compounds and is abundantly expressed in the liver, kidneys, and intestines. The high amino acid similarity between human and porcine CYP1A1 indicates that they probably have the same metabolic characteristics. Therefore, understanding the regulatory mechanism of CYP1A1 expression in pigs is particularly important for predicting the toxicology and metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
1
0
0
1
Order By: Relevance
“…These data indicated that AhR and Sp1 participate in the regulation of CYP1A1 and other CYP450 genes. In this study, we identified the proximal promoter region that contained an overlapping XRE/GC box and determined the basal transactivation of the CYP1A1 gene; our results were consistent with those showing the overlapping XRE/ GC box in the proximal promoter region of porcine CYP1A1, yet in that previous study, only the GC box was involved in regulating basal CYP1A1 expression [57]. Thus, the differences in the CYP1A1 regulatory mechanisms between humans and pigs require further study.…”
Section: Discussionsupporting
confidence: 85%
“…These data indicated that AhR and Sp1 participate in the regulation of CYP1A1 and other CYP450 genes. In this study, we identified the proximal promoter region that contained an overlapping XRE/GC box and determined the basal transactivation of the CYP1A1 gene; our results were consistent with those showing the overlapping XRE/ GC box in the proximal promoter region of porcine CYP1A1, yet in that previous study, only the GC box was involved in regulating basal CYP1A1 expression [57]. Thus, the differences in the CYP1A1 regulatory mechanisms between humans and pigs require further study.…”
Section: Discussionsupporting
confidence: 85%
“…Regulação da transcrição gênica Adjacente à região core, encontra-se a região proximal do promotor, (79) caracterizada como a região onde ocorre a ligação de TFs específicos para a regulação daquele determinado gene, como representado na figura 2-A. (86) A extensão da região promotora total pode variar de 100 a 3000pb upstream ao gene. (87) Uma vez que a molécula de mRNA é transcrita, ela está sujeita a regulação pós-transcricional, que está relacionada às modificações na molécula de mRNA, sendo as principais a poliadenilação, que é a adição de uma cauda poli-A na extremidade 3', composta pela ligação de 80-200 resíduos de adenina, e o capping ou CAP 5'.…”
Section: Regulação Transcricional De Ripk3 E Mlkl: Um Novo Horizonte ...unclassified